Factors affecting the cultural competence of visiting nurses for rural multicultural family support in South Korea - Min Hyun Suk; Won-Oak Oh; YeoJin Im (BMC, 2018)
Abstract Background With the recent growth of multicultural families in the Korean society, the importance of the role of qualified visiting nurses in the delivery of culturally sensitive health care has grown dramatically. As the primary health care provider for multicultural families enrolled in public community-based health care centers, the cultural competence of visiting nurses is an essential qualification for the provision of quality health care for multicultural families, especially in rural areas. Cultural competence of visiting nurses is based on their cultural awareness and empathetic attitude toward multicultural families. This study aimed to examine the levels of cultural competence, empowerment, and empathy in visiting nurses, and to verify the factors that affect the cultural competence of visiting nurses working with rural multicultural families in South Korea. Methods Employing a cross-sectional descriptive study design, data from 143 visiting nurses working in rural areas were obtained. Data collection took place between November 2011 and August 2012. The measurement tools included the modified Korean version of the Cultural Awareness Scale, the Text of Items Measuring Empowerment, and the Interpersonal Reactivity Index to measure the level of empathy of visiting nurses. Analyses included descriptive statistics, a t-test, an ANOVA, a Pearson correlation coefficient analysis, and a multiple linear regression analysis. Results The cultural competence score of the visiting nurses was 3.07 on a 5-point Likert scale (SD = 0.30). The multiple regression analysis revealed that the cultural competence of visiting nurses was significantly influenced by experience of cultural education, empathy, and scores on the meaning subscale of the empowerment tool (R2 = 10.2%). Conclusions Institutional support to enhance visiting nurses' empowerment by assuring the significance of their job and specific strategies to enhance their empathy would be helpful to improve the cultural competence of visiting nurses. Additionally, regular systematic education on culturally sensitive care would be helpful to enable visiting nurses to provide culturally sensitive care for multicultural families.